불완전한 신뢰도 기반 정보 처리율 최대화 협력통신 기법 - 류종열(Jong Yeol Ryu); 홍준표(Jun-Pyo Hong) (한국정보통신학회논문지, 2019)
Recently, the mobile social networks, which consider both social relationship between users and mobile communication networks, have been received great attention. In this paper, we consider the trust degree of node as the social relationship for the cooperative communication networks. In contrast to the existing works that consider the case of the perfect trust degree information, for the case that transmitter has an imperfect trust degree information, we propose an imperfect trust degree based cooperative communication technique that maximizes a throughput. We first model the imperfect trust degree information as a probability distribution and derive the outage probability using the probability distribution. Then, we propose the transmission scheme that maximizes the throughput, which consider both outage probability and transmission rate. The simulation results show that the proposed cooperative transmission scheme outperforms the conventional scheme in terms of the throughput. 최근 친밀도와 신뢰도 같은 사용자들의 사회적 관계와 모바일 통신 네트워크를 동시에 고려한 모바일 소셜 네트워크가 차세대 이동통신 네트워크 모델로 큰 관심을 받고 있다. 본 논문에서는 사회적 관계 중 신뢰도 정보를 기반으로 하는 협력통신 네트워크를 고려한다. 완벽한 신뢰도 정보를 고려했던 기존 연구들과 다르게 송신단에서 불완전한 신뢰도 정보 기반 정보 처리율 최대화 협력 통신 기법을 제안한다. 본 논문에서는 먼저 불완전한 신뢰도 정보를 확률적인 분포로 모델링하고, 신뢰도의 확률 분포를 이용하여 아웃티지 확률을 유도한다. 마지막으로 송신단에서 아웃티지 확률과 정보 전송율을 동시에 고려한 정보 처리율을 최대화하는 전송 기법을 제안한다. 시뮬레이션 결과를 통해 정보 처리율 관점에서 기존 기법들과의 비교를 통해서 제안한 협력통신 기법의 우수성을 증명한다.